STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT BASED ON ITS GENERIC STRUCTURE AT THE TENTH GRADE STUDENT OF VOCATIONAL HIGH SCHOOL - Novia Sartika; Mochamad Nurdin (PROJECT (Professional Journal of English Education), 2019)
Study of language skills in English is pretty important to increase students’ skill in study English. One of the most important skills is writing. It can make students share the ideas into written form in the text or paragraph with the right order of generic structure. The purposes of this study are to find out the students ability in writing descriptive text and to find out whether students writing descriptive are already well organized or not. The research method used qualitative research method. The researchers took 33 students as respondents. The data analysis took from the students’ descriptive text results. Based on the data analysis, the researchers found 15 or 45 % students created the descriptive text and 18 or 55 % students created the report text. It showed 10 or 30 % students created the paragraphs of descriptive text properly based on its generic structure and 5 or 15 % students could not apply it properly. It can be concluded that most of the students’ paragraphs are well organized. Meanwhile, the other students could not make it properly, because they still confused and could not distinguish the differences between descriptive text and report text.